A non-aggregated silicon(IV) phthalocyanine-lactose conjugate for photodynamic therapy. Issue 12 (15th June 2020) - Li, Dong; Hu, Qing-Yan; Wang, Xiao-Zhen; Li, Xingshu; Hu, Jia-Qian; Zheng, Bi-Yuan; Ke, Mei-Rong; Huang, Jian-Dong
Graphical abstract: Highlights: A highly hydrophilic hyphthalocyanine-lactose conjugate was synthesized. It is non-aggregated with high reactive oxygen species generation in aqueous media. It shows high photocytotoxicity against HepG2 cells with an IC50 value of 0.023 μM. It exhibits enhanced in vivo tumor targeting and photodynamic therapeutic efficacy. Abstract: To develop a highly efficient photosensitizer for photodynamic therapy (PDT), we have designed and synthesized a phthalocyanine-lactose conjugate (Pc-Lac ) through axial modification of silicon(IV) phthalocyanine with lactose moieties. With the lactose substituents, Pc-Lac is highly hydrophilic and non-aggregated with efficient reactive oxygen species (ROS) generation in aqueous media. With these desirable properties, Pc-Lac shows high photocytotoxicity and cellular uptake toward HepG2 cells. In addition, in vivo fluorescence imaging shows that Pc-Lac could selectively remain at tumor site, leading to its enhanced photodynamic efficacy against H22 tumor-bearing mice. Therefore, Pc-Lac shows a great potential as a highly efficient molecular photosensitizer for PDT.